Analisis Strategi Pemasaran UMKM Tepung Bumbu ARIEN dengan Metode IFE, EFE, SWOT dan STP - Eny Setyariningsih; Budi Utami (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
Businesses that produce food raw materials or processed foods are one of the promising MSME opportunities, one of the prospects and long-term opportunities which can absorb labor. MSMEs Arien seasoning flour is believed to be able to influence economic growth quickly to develop one of the potential products of food raw materials and is expected to be the economic backbone of the community in the surrounding area. MSMEs Flour Bumbu Arien is one of the ones that produces raw food in the category of traditional food. However, the great potential of MSMEs with Arien Seasoning flour can provide considerable profits, because doing this business does not require large capital but has high economic value and profits. The great potential of the Arien Flour MSMEs has not been able to be utilized properly by entrepreneurs who run businesses in the industry because there are still many of them who have not yet received a significant economic impact from the business they are running. This study aims to (1) examine the marketing strategies that have been implemented by MSMEs in marketing their products. (2) Analyzing the internal and external environmental factors of Arien Flour Bumbu MSME that affect the marketing strategy. (3) Formulate and determine alternative marketing strategies. Research data and information consist of primary data and secondary data. The analytical tools used are the IFE (Internal Factor Evaluation) matrix, the EFE (External Factor Evaluation) matrix, the SWOT matrix (Strenghts, Weaknesses, Opportunities, and Theats), and STP (Segmentation, Targeting, Positioning). Results Based on the SWOT and STP analysis related to Arien Seasoned Flour MSMEs, the marketing strategy used today to market their products is to use direct and indirect marketing to attract all consumers. The results of the analysis of the company's internal factors using the IFE matrix, the company's main strength is a quality product, while the main weakness of the Arien Flour Bumbu MSME is the lack of capital. The total IFE matrix score is 1.730 below the total weight score of 2.0, indicating that the company's internal position is weak in overcoming existing weaknesses with its strengths. The result of the EFE matrix analysis is that the company's main opportunity is the high level of consumer loyalty to the Arien Seasoning Flour product. The main threat from the company is the large number of similar products. The total score of the EFE matrix is ??1.953 above the total weight score of 2.0 indicating that the company is able to respond well to external factors by taking advantage of existing opportunities to overcome threats.